Pengaruh Progressive Muscle Relaxation (PMR) terhadap Kelelahan Kerja pada Pekerja di Home Industri Boyazy Garmindo Colomadu - Devi Gita Asokawati; Lis Sarwi Hastuti (Politeknik Kesehatan Kemenkes Surakarta, 2023)
Background. Work fatigue is part of the common problems that are often encountered in the workforce. Work fatigue can cause a decrease in work efficiency, productivity, work capacity, health and endurance ability which causes work accidents. Progressive muscle relaxation (PMR) is a therapeutic intervention that helps reduce fatigue levels. This study aims to determine the effect of PMR on work fatigue in workers. Research methods. This research is a quantitative research with a pre-experimental design with a one group pretest-posttest design without a control group and the data analysis method used is the paired t-test statistical technique, using the statistical program SPSS version 20. The sampling technique used is total sampling with a sample of 22 people. The research instrument uses the Subjective Self Rating Test. Research result. Based on the paired t-test, it shows that the significance value (p-value) is 0.001 (p <0.05), which means that there is a difference in the value before and after the intervention, so that the research hypothesis is accepted. Conclusion. This study shows that Progressive Muscle Relaxation (PMR) has an effect on reducing worker fatigue at Home Industry Boyazy Garmindo Colomadu. References: 34 (2003-2018) Keywords: Progressive Muscle Relaxation (PMR), Work Fatigue.